PERKEMBANGAN STANDAR AKUNTANSI KEUANGAN DI INDONESIA - FERRY DANU PRASETYA (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
Environment and conditions for the existence of legal, social and economic politics vary between countries lent to different accounting standards as well. Financial Accounting Standards of quality is one of the essential infrastructure to realize such transparacy. Financial Accounting Standards is a frame of reference in the prosedurs relating to financial statement presentation. The existence of the Financial Accounting Standards are needed to form a common procedure in explaining how the financial statements prepared and presented. In Indonesia, the Financial Accounting Standards known as the Financial Accounting Standards (IFRSs) which is a result of the formulation of Indonesian Accounting Principals Committee in 1994, replacing the accounting principles Indonesia in 1984. Financial Accounting Standards consist of a Statement of the basic framework of the preparation and presentation of financial statements. SAk is effective starting date of January 1, 1995. As a guide the preparation and presentation of GAAP financial statement into a binding rule, so that the bias toward an understanding of the postal financial statement can be avoided. Indonesia is the case when the harmonization of GAAP toUS-GAAP to IFRS cause changes in the principles of the rules-based system to a principles-based system. IFRS (International Financial Accounting Standards) is an effort to strengthen the global financial architecture and the search for lasting solutions to the lack of transparency of financial information.